Is Cross-Cultural Communication Influenced by Users' Cultural Identity? A Study on The Overseas Communication of "Wukong" Image: 跨文化传播是否受用户的文化认同心理影响？“悟空”形象的海外传播研究 - Xian, Liu; Rui, Chen (Mandarinable: Journal of Chinese Studies, 2023)
Black Myth-Wukong is an electronic game adapted from the Chinese novel Journey to the West. The game exhibits distinct cross-cultural characteristics in its dissemination process. We believe that individual schema differences can influence users’ cross-cultural acceptance behaviors. Utilizing comment data collected from the internet, we conducted a programmatic grounded approach to study and process the data. Our research revealed that users’ schema differences can lead to individuals developing different cultural psychologies, including cultural identification, cultural resonance, and so on. These cultural psychologies may ultimately impact the cross-cultural dissemination of artistic works.